Stres akibat Konflik Peran Ganda dan Coping Stress pada Ibu yang Bekerja dari Rumah selama Pandemi - Ivana Thania; Sasha Pinastika Pritasari; Vanessa Theresia; Tesha; Andrew Franklin Suryaputra; Immanuel Yosua (Jurnal Ilmiah Psikologi MIND SET, 2021)
The Covid-19 pandemic caused working mothers to work from home, while simultaneously taking care for their family especially their children, as well as their daily household chores. Should things continue to be the same, working mothers might experience stress due to conflict of having multiple roles. The purpose of this research is to draw an overview of stress induced by having multiple roles experienced by working mothers, paying attention to their ways to alleviate the stress as well. Research was conducted using phenomenology qualitative method, collecting data in interviews with subjects of three (3) working mothers working from home in pandemic, have children ranging from zero (0) to twelve (12) years old of age, and currently not having any forms of household assistance such as maids and/or butlers to assist them reducing their roles in taking care of daily household chores. Research output yields answers that working mothers do experience stress from having multiple roles that conflict in terms of time, strain, and behavior. Various stress-coping strategies such as being more active, constructing plans, accepting stressful conditions, seeking religious aid, also seeking both instrumental and emotional aid, are being utilized. Research output also indicates that practice of working from home during the pandemic yields potential to induce stress to work-from-home working mothers as consequences of having multiple roles conflicting one another. Helping aids from work environment and family are needed to assist working mothers to help them deal with said conflicts.